Quorum Sensing in Bacillus thuringiensis Is Required for Completion of a Full Infectious Cycle in the Insect - Leyla Slamti; Stéphane Perchat; Eugénie Huillet; Didier Lereclus (Toxins, 2014)
Bacterial cell-cell communication or quorum sensing (QS) is a biological process commonly described as allowing bacteria belonging to a same pherotype to coordinate gene expression to cell density. In Gram-positive bacteria, cell-cell communication mainly relies on cytoplasmic sensors regulated by secreted and re-imported signaling peptides. The Bacillus quorum sensors Rap, NprR, and PlcR were previously identified as the first members of a new protein family called RNPP. Except for the Rap proteins, these RNPP regulators are transcription factors that directly regulate gene expression. QS regulates important biological functions in bacteria of the Bacillus cereus group. PlcR was first characterized as the main regulator of virulence in B. thuringiensis and B. cereus. More recently, the PlcR-like regulator PlcRa was characterized for its role in cysteine metabolism and in resistance to oxidative stress. The NprR regulator controls the necrotrophic properties allowing the bacteria to survive in the infected host. The Rap proteins negatively affect sporulation via their interaction with a phosphorelay protein involved in the activation of Spo0A, the master regulator of this differentiation pathway. In this review we aim at providing a complete picture of the QS systems that are sequentially activated during the lifecycle of B. cereus and B. thuringiensis in an insect model of infection.